Two-year outcomes of patients with atrial fibrillation treated with rivaroxaban: results from RIVER registry. (14th October 2021) - Beyer-Westendorf, J; Camm, A.J; Virdone, S; Fox, K.A.A; Pieper, K.S; Le Heuzey, J.-Y; Haas, S; Kayani, G; Gersh, B.J; Turpie, A.G.G; Kakkar, A.K; ,
Abstract: Introduction: Non-vitamin-K oral anticoagulants (NOACs) were recommended in preference to oral vitamin K antagonists (VKAs) in the 2020 updated guidelines for stroke prevention in atrial fibrillation (AF), from the European Society of Cardiology (ESC). Rivaroxaban is a NOAC that is approved in many countries worldwide for reducing the risk of stroke or systemic embolism in patients with nonvalvular atrial fibrillation (AF). Purpose: To explore the baseline characteristics, dosing and 2-year outcomes of patients with AF treated with rivaroxaban. Methods: RIVaroxaban Evaluation in Real Life setting (RIVER) is a prospective international, multicenter registry of patients with newly diagnosed non-valvular AF treated with rivaroxaban for the prevention of thromboembolic stroke and at least one investigator-determined risk factor for stroke. Results: A total of 5043 patients were enrolled into RIVER between January 2015 and June 2017. Mean (SD) age at diagnosis was 69.5 (11.0) years and 55.7% were males. Caucasian patients represented the largest proportion of patients in RIVER (80.3%), followed by Asians (5.5%) and hispanic/latino (3.7%). Almost all patients (98.5%) were prescribed a single daily dose of rivaroxaban, most commonly 20 mg (77.3%) and 15 mg (20.4%), while a 10 mg dose was prescribed in only 2.3% of patients. During the 2-year follow-up, the rates (95% CI) of all-cause mortality, stroke/SE, and major bleeding were 2.75 (2.43 to 3.12), 0.89 (0.72; 1.11), and 1.26 (1.05 to 1.52) per 100 person years, respectively (Figure 1). The most common cardiovascular cause of death was congestive heart failure (30.4%) and myocardial infarction (11.4%). Leading non-cardiovascular causes of death were malignancy (27.4%), respiratory failure (18.9%) and infections/sepsis (13.2%). Over 2 years, 710 (14.1%) of patients discontinued rivaroxaban. The corresponding proportions at 6 months and 1 year were 7.8% and 10.8%, respectively. Out of all the patients who discontinued, 62 (8.7%) restarted rivaroxaban during their follow-up (Table 1). Conclusion: During 2 years of follow up in the international, prospective RIVER registry, rivaroxaban treatment for AF was associated with low rates of stroke or major bleeding. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by an unrestricted research grant from Bayer AG, Berlin, Germany, to TRI, London, UK. This work is supported by KANTOR CHARITABLE FOUNDATION for the Kantor-Kakkar Global Centre for Thrombosis Science.